ANALISIS PENYEBAB KECACATAN DAN USULAN PERBAIKAN PRODUK CETAK INDUSTRI PERCETAKAN PT. XYZ DENGAN METODE FMEA - Setiawan, Muhammad Rifki; Purnama, Agus Rachmad (SISTEM Jurnal Ilmu Ilmu Teknik, 2025)
PT. XYZ is a company engaged in printing that produces printed products for books, brochures, pamphlets and other promotional materials. Customer complaints about printed products produced throughout 2024, there were a total of 110 complaints from a total of 2404 customer complaints documented from the beginning of its operation in 1990 to 2024. These complaints generally concern 10 types of printed product defects, including: color defects, miss register, bad plong, dented box, bad cutting, uv defects, defective plates, and hotprint defects. This study is intended to analyze the factors causing product defects from the perspective of functional failure of production components/equipment that result in defects using the FMEA method, and provide improvement suggestions with the 5W + 1H approach. Based on the analysis with the Pareto diagram, the most dominant defects include: a. color defects (28.24%), b. miss register (27.29%), and bad plong (24.47%), where through the FMEA method, 7 components were obtained with risk priority number (RPN) ​​above the critical value threshold (RPN ≥82), with the main priority being the register sensor component (RPN = 168), spray nozzle (RPN = 108) and worn cylinder bearing (RPN = 105). Proposed improvements with the 5W + 1H approach, it is recommended to carry out a. routine sensor calibration and replacement if worn, b. periodic inspection, sharpening, and blade replacement, c. stabilize the voltage, d. select quality plates.